AGAMA PRA-ISLAM DI NUSANTARA: KARAKTERISTIK BUDAYA DAN SINKRETISME DARI ANIMISM HINGGA HINDU-BUDDHA - M. Fadlilul Ibad; Nikmatul Khusnah; Azarotul Firdausi; Anang Sholikhuddin (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
Pre-Islamic religion and culture in the Archipelago had diverse characteristics and had been deeply rooted before the arrival of Islam. The people of the Archipelago in the pre-Islamic period adhered to animism and dynamism belief systems, later overlaid by Hindu-Buddhist influences that came afterward. This article aims to describe the characteristics of pre-Islamic religion and culture in the Archipelago, including belief systems, ritual practices, social structure, politics, education, literature, and architecture. Using a library research method with a historical approach, this study finds that pre-Islamic religion in the Archipelago has distinctive features such as belief in ancestral spirits, worship practices at sacred sites, a caste system (Hindu influence), and terraced shrines (punden berundak) as the forerunner of temple architecture. These cultural characteristics later became an important foundation for the acculturation process when Islam entered the Archipelago